2010
DOI: 10.1007/s11325-009-0322-y
|View full text |Cite
|
Sign up to set email alerts
|

Auto bi-level with pressure relief during exhalation as a rescue therapy for optimally treated obstructive sleep apnoea patients with poor compliance to continuous positive airways pressure therapy—a pilot study

Abstract: Auto bi-level with pressure relief during exhalation treats OSA as effectively as CPAP without inducing additional arousals. Transitioning non-compliant CPAP patients without modifiable causes of poor compliance from their CPAP to this new device improves compliance and clinical outcomes over a 10-week period.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
18
1
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 35 publications
3
18
1
1
Order By: Relevance
“…7 However, in patients requiring an effective CPAP level higher than 10 cm H 2 O there was a greater significant improvement in mean usage/night. In a randomized controlled trial, Ballard et al found that, changing to flexible bilevel airway pres sure therapy improved compliance in patients previously not compliant with CPAP therapy.…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations
“…7 However, in patients requiring an effective CPAP level higher than 10 cm H 2 O there was a greater significant improvement in mean usage/night. In a randomized controlled trial, Ballard et al found that, changing to flexible bilevel airway pres sure therapy improved compliance in patients previously not compliant with CPAP therapy.…”
Section: Discussionmentioning
confidence: 92%
“…Bilevel-auto was proposed as an alternative to CPAP as a rescue therapy in the presence of poor compliance or tolerance. 7,[11][12][13] A validation study performed in OSAS patients naïve to CPAP treatment, compared the efficacy of Bilevel-auto against standard CPAP and subjective and objective compliance over 90 days of use. 6 Authors did not find statistically significant differences in efficacy or compliance between the two treatments, raising the question of whether Bilevel-auto could be considered as an alternative therapy in patients not tolerating CPAP.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These have included auto-bi-level pressure relief-positive airway pressure (ABPR-PAP). Four studies [64][65][66][67] showed similar improvements in symptoms using an auto-bi-level mode and CPAP. Compliance was generally beter with the auto-bi-level modes than CPAP, even in CPAP patients selected for poor compliance [65,67].…”
Section: Update On Pap Devicesmentioning
confidence: 86%